Early Career Teacher Agency in K–12 Education : A Scoping Review of Empirical Studies - Jeong, Eunji (2024)
The perspective of early career teachers (ECTs) in need of support has often been criticized for leaving their potential and strengths out of view. Researchers have explored the concept of teacher agency to understand how ECTs take proactive roles in their induction and development, beyond the view that they are immature. This scoping review aimed to provide an overview of empirical studies published between 2018 and 2022, focusing on ECT agency in K–12 education. In particular, this research investigated how the previous studies approached ECT agency methodologically, conceptually, and practically.